Management of Family Education in Growing Anti-Sexual Violence Attitudes - Werdiningsih, Wilis; Winursito, Yekti (ASANKA : Journal of Social Science and Education, 2024)
Sexual violence against children is a crime that must be eliminated. This sexual violence has a negative impact on both physical and psychological aspects. Children are seen from two sides, namely children with potential as perpetrators and children with potential as victims. In this regard, parents have full responsibility to ensure that their children are not perpetrators, let alone victims of sexual violence. This study aims to analyse efforts to suppress the number of sexual violence through family education management in instilling an anti-sexual violence attitude. The approach used in this research is literature study. Data were obtained from various sources from articles and relevant reference books, related to the definition of sexual violence, acts of sexual violence, impacts and efforts to prevent sexual violence and the role of parents in preventing sexual violence. These various sources were analysed as findings from writing this article, which are related to family education management in instilling an anti-sexual violence attitude. The results show that the management of family education that is carried out by parents well can encourage children to understand and have an anti-sexual violence attitude. Thus, it is hoped that in the lives of children, children are protected from being perpetrators of sexual violence and as victims. Management of education in this family can be done by example, good communication between parents and children, and the cultivation of religious knowledge.